2000
DOI: 10.1046/j.1471-4159.2000.0750701.x
|View full text |Cite
|
Sign up to set email alerts
|

The Triakontatetraneuropeptide (TTN) Stimulates Thymidine Incorporation in Rat Astrocytes Through Peripheral‐Type Benzodiazepine Receptors

Abstract: Astrocytes and astrocytoma cells actively express the diazepam-binding inhibitor (DBI) gene, suggesting that DBI-processing products may regulate glial cell activity. In the present study, we have investigated the possible effect of one of the DBI-derived peptides, the triakontatetraneuropeptide (TTN), on [ H]thymidine incorporation, whereas the central-type benzodiazepine receptor antagonist flumazenil (10 Ϫ6 M) had no effect. The present study demonstrates that the endozepine TTN stimulates DNA synthesis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 51 publications
5
16
0
Order By: Relevance
“…It has previously been shown that TTN is one of the major forms of endozepines released by cultured astroglial cells (Patte et al, 1999;Gandolfo et al, 2000). We now demonstrate that TTN, acting through PBR, causes calcium influx through L-type calcium channels in cultured rat astrocytes.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…It has previously been shown that TTN is one of the major forms of endozepines released by cultured astroglial cells (Patte et al, 1999;Gandolfo et al, 2000). We now demonstrate that TTN, acting through PBR, causes calcium influx through L-type calcium channels in cultured rat astrocytes.…”
Section: Discussionsupporting
confidence: 54%
“…In the brain, the DBI gene is predominantly expressed in glial cells (Tong et al, 1991;Lihrmann et al, 1994;Alho et al, 1995) and the occurrence of DBI-derived peptides has been visualized in astrocytes by immunohistochemistry (Tonon et al, 1990;Malagon et al, 1993;Vidnyanszky et al, 1994;Do-Ré go et al, 2001). It has also been shown that cultured rat glial cells contain and secrete DBI-related peptides (Lamacz et al, 1996;Patte et al, 1999), and that TTN is the major form of endozepines released by astroglial cells (Gandolfo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The release of endozepines by cultured glial cells can be inhibited by GABA or somatostatin (14,15) and stimulated by beta-amyloid peptide or pituitary adenylate cyclase-activating polypeptide (16)(17)(18). DBI peptides also have been demonstrated to affect astrocytic function via actions on the mitochondrial benzodiazepine receptor, also known as 18-kDa translocator protein, which influences GABA receptor activation through modulation of neurosteroid production (19,20). Endogenous regulation of endozepine actions by native glial cells and subsequent effects on synaptic inhibition remain to be demonstrated.…”
mentioning
confidence: 99%
“…Fourth, the selective PBR antagonist PK11195 markedly reduced [ 3 H]thymidine incorporation in rat astrocytes induced by low-dose triakontatetraneuropeptide (TTN), a DBI-derived peptide. In contrast, the selective CBR antagonist flumazenil did not significantly modify the effect of TTN (32). Further research is, however, needed to elucidate whether the inhibition of salivary secretion by repetitive administration of DZP is attenuated by simultaneous treatment with a peripheral-type benzodiazepine antagonist.…”
Section: +mentioning
confidence: 88%